Utilization of Edpuzzle Media to Improve Students' Reading Comprehension Skills at Indonesian Schools in Jeddah - Alfisyah, Alfisyah; Supartinah, Supartinah; Riyanto, Dwi Mahmud Rizki (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2025)
Reading comprehension is an important aspect that students must be taught. One alternative to improving reading comprehension skills is using Edpuzzle media. This study aims to improve the reading comprehension abilities of students in Grade II D of the Indonesian School in Jeddah, Saudi Arabia, by utilizing Edpuzzle media. In this study, the method used was classroom action research, which used a model developed by Kemmis and Mc. Taggart. The subjects of the study were grade II D students at the Indonesian School of Jeddah. The study involved 32 students, comprising 13 boys and 19 girls. The data collection techniques used were observation, tests, and documentation. The research instrument consisted of observation sheets and tests. The data analysis technique employed in this study utilized a qualitative data analysis approach, consisting of three stages, as described by Miles and Huberman, in addition to quantitative data analysis. The results show a significant increase in the average reading comprehension score, from 44.82 in the pre-cycle to 82.41 in the second cycle, and an increase in classical completeness from 18.51% to 93%. In addition, the implementation of learning. Additionally, the learning implementation rate increased from 60% in the first cycle to 80% in the second cycle. Thus, the use of Edpuzzle has been proven effective in improving students' understanding.